A combined treatment using ethylmethane sulfonate and ultraviolet light to compare amylase production by three Bacillus sp. isolates. Issue 9 (21st October 2018) - Karakus, Betul Zehra; Korkmaz, İlknur and Demirci, Kubra and Sinan Arslan, Kadir and Unlu, Ozge and Catal, Tunc
Abstract: In this study, three Bacillus sp.-producing amylase enzymes were isolated from soil samples and identified using 16S rDNA sequence analysis. Amylase production and total protein productions were spectrophotometrically measured. The following media were tested to increase enzyme production: LB medium and molasses. Three Bacillus sp. were identified as follows: Bacillus subtilis subtilis, Bacillus thuringiensis, and Bacillus cereus. Amylase production levels were in the range of 10 U/mL, whereas total protein production levels were at 15 mg/mL. Higher amylase activity was found in the Bacillus subtilis isolate. Ethylmethane sulfonate (EMS) and ultraviolet (UV) mutagenesis in combination were applied to compare amylase production. Amylase activity was increased to around 58% in the treatment with 0.03 mL of EMS and UV when compared to the control group. A pilot scale bioreactor with a total working volume of 10 liters was used to produce amylase by B. subtilis subtilis . In conclusion, B. subtilis subtilis can be used to produce amylase enzyme for various industrial purposes, and, for the first time, the amylase activities of B. subtilis can be enhanced with EMS and UV treatment.